Everything is illuminated : a novel - Foer, Jonathan Safran, 1977- (Boston [Mass.] : Houghton Mifflin Co., 2002)
American college student Jonathan Safran Foer sets out, along with Ukranian travel agent Alex Perchov, Alex's depressive grandfather, and the family dog, in an attempt to find the village where a Ukranian woman might or might not have saved Jonathan's grandfather from the Nazis during World War II.
Adult
Adult
Wilson's Fiction
Library Journal Starred
Booklist starred
880L
Keywords: Americans -- Ukraine -- Fiction; World War, 1939-1945 -- Ukraine -- Fiction; Grandfathers -- Fiction; Novelists -- Fiction; Young men -- Fiction; Ukraine -- Fiction; Americans -- Ukraine -- Fiction; World War, 1939-1945 -- Ukraine -- Fiction; Grandfathers -- Fiction; Novelists -- Fiction; Young men -- Fiction; Ukraine -- Fiction; Humorous fiction; Domestic fiction; Bildungsromans; Humorous fiction; Domestic fiction; Bildungsromans